Anomalous Papillary Muscle Insertion as a Cause of Mitral Regurgitation: Multimodality Imaging–Based Diagnosis. (December 2020) - Nalawade, Digvijay; Borikar, Nikhil; Bawaskar, Parag; Chaurasia, Ajay
Abstract : Supplemental Digital Content is available in the text.